The Role of Female Farm Workers in the Economic Resilience of Families in Koto Balingka District, West Pasaman District - Sahara, Elfi; Bahar, Muchlis; Duhriah, Duhriah (Institut Agama Islam Negeri (IAIN) Curup, 2024)
Purpose:This research aims to explore the contribution of female agricultural workers in strengthening family economic resilience from a sharia economic perspective.Design/Method/Approach:This research is field research with a qualitative descriptive approach. The informants in this research were 10 female farm workers in Koto Balingka District. Data collection techniques include observation, interviews and documentation and data analysis techniques used are data reduction, data presentation and drawing conclusions.Findings: The research results highlight the significant role of female agricultural workers in three main aspects of agricultural activities, namely planting, weeding and harvesting.Among the three forms of agricultural labor, women tend to dominate the role in weeding and harvesting in the agricultural sector. Not only are there differences in the division of labor, but in terms of wages there are also differences where women's wages are IDR 80,000 per day, while men's wages are IDR 100,000.Factors that encourage women to work as agricultural laborers include difficult economic conditions, low levels of education, and limited employment opportunities. Their participation has a very important impact on the economic security of the family, because their contribution helps improve the economic stability of the household. However, we need to recognize that there are negative impacts, such as changes in traditional roles within the family. The role of female agricultural workers in increasing family economic resilience can also be understood from a sharia economic perspective. By paying attention to indicators of family economic resilience, their role can be considered to have made a significant contributionOriginality/Values: this research analyzes the economic contribution of female agricultural workers to the family's income and economic resilience from a sharia economic perspective. This research aims to evaluate the role of gender in agricultural activities and assess the economic welfare of the families of female agricultural workers within the framework of sharia economics.